2020
DOI: 10.1172/jci133008
|View full text |Cite
|
Sign up to set email alerts
|

Graft IL-33 regulates infiltrating macrophages to protect against chronic rejection

Abstract: temic expansion of ST2 + Tregs (29,30). IL-33 expressed by fibrogenic/adipogenic progenitors in skeletal muscle has also been shown to regulate skeletal muscle Treg homeostasis and support muscle regeneration (31). Related studies have suggested a direct, cardioprotective role for rIL-33 against hypertrophy resulting from cardiac overload (32) and fibrosis after myocardial infarction (33). However, delivery of rIL-33 also aggravates autoimmune eosinophilic pericarditis during coxsackievirus B3 infection (34), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
70
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(71 citation statements)
references
References 94 publications
1
70
0
Order By: Relevance
“…Using a mouse model of chronic rejection following heart transplant, Li et al 3 showed that the lack of IL-33 expression in the transplanted heart accelerates graft rejection, associated with increased T-cell infiltration. In light of these observations IL-33 emerges as a stromal cell-derived alarmin which limits the local inflammatory response early after transplantation (Figure).…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Using a mouse model of chronic rejection following heart transplant, Li et al 3 showed that the lack of IL-33 expression in the transplanted heart accelerates graft rejection, associated with increased T-cell infiltration. In light of these observations IL-33 emerges as a stromal cell-derived alarmin which limits the local inflammatory response early after transplantation (Figure).…”
mentioning
confidence: 99%
“…Indeed, IL-33 is upregulated in allografts and its absence significantly aggravates vascular occlusion and subsequent fibrosis in the transplanted tissue. 3 …”
mentioning
confidence: 99%
See 3 more Smart Citations